Current Methods for Statistical and Logical Estimation of Significance of Genetic Matches Might Not Always be Appropriate - Beer, Zsuzsanna (Array, 2004)
Background and purpose: Today it is generally accepted that STR sequences can provide sufficient information to determine identity or paternity in most forensic cases. Elaborate statistical methods have been developed to quantify the significance of genetic matches, but the calculated numbers have never been validated in "real" situations. As a part of the process of identification of war victims in Croatia we have randomly matched hundreds of genotypes and observed unexpectedly high number of statistically improbable matches between unrelated people. We speculated that this might be a consequence of higher than expected frequency of specific combinations of some STR alleles. Material and methods: Using an in-house developed computer program we generated all possible combinations of alleles on all possible three-locus combinations of STR loci covered by AmpFLSTR Profiler Plus kit (D3S1358, vWA, FGA, D8S1179, D21S11, D18S51, D5S818, D13S317, and D7S820). Two sets of genotypes were analyzed. One set consisted of 201 unrelated individuals from Hungary, and the other of 295 unrelated individuals from Croatia Results and conclusion: We have calculated frequencies of all possible three-locus haplotype combinations and determined that some combinations are much more frequent than expected. Different combinations of alleles were found to be most frequent in Croatian and Hungarian populations, what supported the hypothesis that these aberrations from expected values might be population-specific. Probabilities of complete 9-loci haplotypes calculated by combining frequencies of three-locus haplotypes can be significantly different from probabilities calculated using individual alleles, suggesting that currently used statistical methods might not be accurate in genotypes that contain these over-abundant mini-haplotypes.